Challenges in the Creative Process within Romanian Advertising Agencies: Obstacles and Solutions - Mădălina Moraru (Buga-Moraru) (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The creative industry daily faces genuine challenges in their work when it comes to advertising and meeting client's demands. Besides, technology and the necessity of updating creativity resources urge on new approaches during campaigns, at least in creative department. Extrinsic and intrinsic motivation stand for essential aspects in challenging new resources of creativity in a field where copywriters and art directors unfold incredible sensitive messages following strong and relevant insights. The present paper aims to point out the difficulties and opportunities of creative work in any advertising agency, by exploring the purpose, the barriers and the chances of this activity in the context of a complex relationship between client-brand management-consumers. One could perhaps say that these employees are just gifted people able to simply follow some instructions given by the planning department. Actually, they have their own psychological and even social barriers or engines, which represent challenges. Therefore, we have investigated these issues by conducting semi-structured interviews based on their creative experiences in both cases, as juniors and seniors, respectively. The data collected via semistructured interviews are investigated by using content analysis.
Keywords: M37; 330; advertising; creativity; challenges; copywriting; success; brands